2019
DOI: 10.7717/peerj.7953
|View full text |Cite
|
Sign up to set email alerts
|

Demographic history and population genetic analysis of Decapterus maruadsi from the northern South China Sea based on mitochondrial control region sequence

Abstract: Late Pleistocene climate oscillations are believed to have greatly influenced the distribution, population dynamics, and genetic variation of many marine organisms in the western Pacific. However, the impact of the late Pleistocene climate cycles on the demographic history and population genetics of pelagic fish in the northern South China Sea (SCS) remains largely unexplored. In this study, we explored the demographic history, genetic structure, and genetic diversity of Decapterus maruadsi, a typical pelagic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Our phylogeographic and population genetic surveys at cytb gene revealed a genetic homogeneity in P. macrocephalus and most P. anea L2 South China Sea populations ( Table 3 and Table 4 ). The same finding was also reported in the other marine fishes Thamnaconus hypargyreus [ 80 ]; Thunnus tonggol [ 81 ]; Pampus chinensis [ 82 ]; Decapterus maruadsi [ 83 ]. Population expansion that may facilitate wide distribution and present genetic exchange among the populations may explain this.…”
Section: Discussionsupporting
confidence: 82%
“…Our phylogeographic and population genetic surveys at cytb gene revealed a genetic homogeneity in P. macrocephalus and most P. anea L2 South China Sea populations ( Table 3 and Table 4 ). The same finding was also reported in the other marine fishes Thamnaconus hypargyreus [ 80 ]; Thunnus tonggol [ 81 ]; Pampus chinensis [ 82 ]; Decapterus maruadsi [ 83 ]. Population expansion that may facilitate wide distribution and present genetic exchange among the populations may explain this.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have suggested that there were unlimited migrations between the South China Sea and the adjacent seas [7,16,55]. Within the South China Sea, previous studies also displayed unlimited migrations among populations [4,14,15,34,56].…”
Section: Genetic Structure and Diversitymentioning
confidence: 94%
“…We used the species from genus Trachurus ( T. declivis , T. japonicus , T. mediterraneus , T. novaezelandiae , T. picturatus , and T. trachurus ) as the distal outgroup. We set up three competing scenarios for time-calibration in the BEAST analyses, which are (1) the time-calibration based on the evolutionary rate, 3% to 10% per million years (My), of control region 33 , 34 ; (2) the divergence of M. cordyla populations occurred in the last glacial maximum (LGM) in ~ 250,000 years ago 35 ; (3) the divergence of M. cordyla populations occurred in the Pleistocene (~ 2.0 My ago, Mya). In the time-calibrated BEAST analyses, we applied an uncorrelated relaxed clock for independent branch rates, Yule model for speciation, and GTR + I + G model for nucleotide substation for all three BEAST analyses.…”
Section: Methodsmentioning
confidence: 99%
“…4). A molecular clock configured to a rate of 3-10% genetic divergence in the control region per million years (My) 33,34 revealed a split between the Singapore and Indonesia genotypes roughly 0.44 ± 0.287 My ago (Mya). The divergence date of M. cordyla populations calibrated using the time of the last glacial maximum (LGM) 35 was 0.012 ± 0.055 Mya.…”
Section: Hypothesis Testing Of Diversification Periodsmentioning
confidence: 99%